La frontera entre rejas de papel - Miguel Ángel Melón Jiménez (Mélanges de la Casa de Velázquez, 2014)
As the Modern Age progressed, States exhibited a growing interest in surveillance and control of the frontiers upon which their sovereignty rested. Their margins, for the most part unstable, were inhabited by characters who traded illegally in goods as a livelihood or as a means of enrichment. In Spain, the body responsible for their prosecution was the Resguardo de Rentas, and exceptionally the Army when the crimes committed by smugglers and bandit-smugglers were so outrageous as to overstep all bounds and thus required exceptional measures. The subject of this paper is then the lists naming and identifying these outlaws and the officers of the law who combated them.